Postpacking Sweet Cherry Stem and Fruit Quality Attributes Influenced by Cultivar - Rachel Leisso; Janet Turner; Shawn McMurtrey; Emmi Klarer; Jade Emmons; Jacob Wiessner; Kevin Wang; Eric Wang; Christopher Imler (HortTechnology)
Sweet cherries (Prunus avium) destined for traveling to export markets must retain fruit and stem quality for 2 to 5 weeks postharvest. This 2-year study evaluated commercially sorted and packed sweet cherry cultivars (Chelan, Black Pearl, Bing, Regina, Skeena) fruit and stem quality outcomes following 4 weeks of storage at −0.6 ± 0.5 °C or 4.4 ± 0.5 °C in modified atmosphere (MA) bags. Cultivar-specific influences on physiochemical quality outcomes included pedicel fruit retention force, fruit firmness, color, soluble solids content, and titratable acidity at 4 weeks postharvest. A comparison of quality attribute changes within each lot between the initial evaluation and 4 weeks postharvest indicated that color and firmness changed with regard to cultivar, with Skeena having the least change in firmness and Bing undergoing the most darkening. Many visual attributes, including stem weight-to-length ratio (an indicator of thickness or desiccation), stem retention, fruit cracking, pitting, and pebbling, were not statistically influenced by cultivar, indicating that in a commercial setting, lot-to-lot differences in horticultural, harvest, and packing management influence stem and fruit quality outcomes as much as cultivar. Stems with the distal end removed by packinghouses’ cluster-cutter had lower stem weight-to-length ratios than those of stems that did not have their ends removed, indicating that this aspect of packing leads to desiccation of cut stems. Packinghouse (four in 2023 and five in 2024) did not statistically influence fruit or stem quality. Respiration rates differed among cultivars, with Black Pearl exhibiting the lowest and Regina exhibiting the highest; overall respiration rates were higher at 4.4 °C. There were significant (P < 0.05) but weak (approximately Spearman r2 = 0.50) correlations between respiration rates at 1 week and fruit quality attributes at 4 weeks postharvest [increased loss of stems, decrease in pitting and pebbling incidence, and a change in a* (red/green fruit color component derived from colorimeter instrumentation)]. In a multivariate analysis, ‘Black Pearl’ and ‘Chelan’ lots stored at −0.6 °C typically were closest to an “ideal” lot of sweet cherries. Understanding cultivar-specific quality attributes as well as the impact of management decisions can aid in new planting choices, strategic planning in packinghouses, and proactive treatment to mitigate quality loss.